Reforming the Incident Management System in the Health System: A Perspective Article - Ali Mohajervatan; Fatemeh Rezaei (Health in Emergencies & Disasters Quarterly, 2023)
Background: A coordinated disaster response needs a well-organized structure and a locally adapted framework. In light of this, the COVID-19 pandemic offered an opportunity to renovate the response structure, which exhibited deficiencies during the pandemic. Iran shares the experience of an integrated response structure named the reform incidents command system (RICS). It includes an integrated approach in which the organization lacks a unified commander in favor of a set of goals. Materials and Methods: This perspective article shows how Iran can develop its national disaster management system as seen through an expert’s review perspective. Results: This paper elaborates on the RICS concept. This concept removes the challenges of unifying different thoughts and objectives by instilling a shared mental model to improve teamwork. Conclusion: This is one of the first articles to discuss the main joint goals of team members, encouraging collaboration between different parts of the team when interdependent organizations must coordinate their responses.